Zirconia ceramics and preparation method thereof and electronic product housing

By adjusting the element content and composition of zirconia ceramics, combined with wet grinding and sintering processes, zirconia ceramics with low light transmittance, high impact resistance, low density and easy processability were prepared, which solved the problem of the inability to simultaneously in the prior art. The problem of combining these characteristics meets the performance demand for electronic product shells in the 5G era and reduces production costs.

CN116535206BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210095790.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2025-01-14
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

Existing zirconia ceramics cannot have both low density, low dielectric constant, high impact resistance, low light transmittance and easy processability, and it is difficult to meet the demand for improving dielectric constant and density in the 5G era.

Method used

By adjusting the content and composition of Zr, Y, Ln, and Al in the zirconia ceramic, a zirconia ceramic containing 30-63 wt% tetragonal phase zirconia and 37-70 wt% secondary phase, the secondary phase contains LnAl11O18 and/or LnAlO3. Combined with wet grinding and sintering processes, the microstructure of the ceramic is optimized to achieve low light transmittance, high impact resistance, low density and easy processability.

Benefits of technology

It realizes the low light transmittance, low dielectric constant, low hardness, high toughness and easy processing of zirconia ceramics, meets the performance requirements of electronic product shells in the 5G era, simplifies the process flow and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003490961630000191
    Figure BDA0003490961630000191
  • Figure BDA0003490961630000201
    Figure BDA0003490961630000201
  • Figure BDA0003490961630000202
    Figure BDA0003490961630000202
Patent Text Reader

Abstract

The present invention relates to the technical field of zirconia ceramics, and in particular to a zirconia ceramic and a preparation method thereof and an electronic product housing. Based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements: 20.65-59.18wt% of Zr, 0.82-3.01wt% of Y, 7.07-53.03wt% of Ln, 3.49-28.7wt% of Al, where Ln is selected from at least one of La, Eu, Nd, Gd, Ce and Sm; and the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia and 37-70wt% of a secondary phase, and the secondary phase comprises LnAl 11 O 18 And / or LnAlO3. The zirconia ceramic provided by the present invention simultaneously meets the following requirements: low light transmittance, high impact resistance, low density, low dielectric constant, low hardness, high toughness and easy processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zirconia ceramics, and in particular to a zirconia ceramic and a preparation method thereof, and an electronic product housing. Background Art

[0002] Zirconia ceramics have the characteristics of good corrosion resistance, high hardness and high strength of conventional ceramics, so they are widely used. Its toughness (reaching 5-6MPa·m 1 / 2 ) is higher than other conventional ceramics, but it has the disadvantage of weak impact resistance when made into large-area appearance parts; in addition, when it is prepared into a mobile phone back cover product, due to its thin thickness, the semi-transparency of the zirconia ceramic itself will be magnified, so it is necessary to introduce a process of coating ink on the back to prevent the internal components from being seen, thereby increasing the cost; in addition, with the advent of the 5G era, customers have higher and higher requirements for dielectric constant and density, and reducing dielectric constant and density has become an urgent issue. Therefore, it is very important to develop a zirconia ceramic with low density, low dielectric constant, high impact resistance and good processability for the application of ceramic back covers in the 5G era. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems that existing zirconia ceramics cannot have low density, low dielectric constant, high impact resistance, low light transmittance and easy processing at the same time, and to provide a new zirconia ceramic and a preparation method thereof and an electronic product housing. The zirconia ceramic has low light transmittance and high impact resistance, and also has the characteristics of low density, low dielectric constant, low hardness, high toughness and easy processing.

[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a zirconia ceramic, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements: 20.65-59.18wt% Zr, 0.82-3.01wt% Y, 7.07-53.03wt% Ln, 3.49-28.7wt% Al, wherein Ln is selected from at least one of La, Eu, Nd, Gd, Ce and Sm; and the zirconia ceramic comprises: 30-63wt% tetragonal zirconia and 37-70wt% secondary phase, and the secondary phase comprises LnAl 11 O 18 and / or LnAlO3.

[0005] Preferably, in the zirconia ceramic, LnAl 11 O 18 It exists in the form of whiskers, and LnAlO3 exists in the form of perovskite.

[0006] Preferably, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 38.61-56.36wt% Zr, 1.09-2.86wt% Y, 7.64-45.45wt% Ln, 3.78-24.6wt% Al; the zirconia ceramic includes: 40-60wt% tetragonal zirconia and 40-60wt% secondary phase.

[0007] A second aspect of the present invention provides a method for preparing a zirconia ceramic, the method comprising the following steps:

[0008] (1) adding water, a dispersant and a binder to powders of zirconium oxide containing yttria, lanthanide oxides and aluminum oxide for wet grinding to obtain a slurry;

[0009] (2) drying the slurry to obtain composite zirconium oxide powder;

[0010] (3) molding and sintering the composite zirconium oxide powder in sequence to obtain a zirconium oxide ceramic;

[0011] Wherein, Ln in the lanthanide oxide is selected from at least one of La, Eu, Nd, Gd, Ce and Sm;

[0012] The molar ratio y of the lanthanide oxide and aluminum oxide satisfies: 1:11≤y≤1:1, wherein the lanthanide oxide is calculated as Ln and the aluminum oxide is calculated as Al.

[0013] The third aspect of the present invention provides a zirconia ceramic prepared by the method provided in the second aspect.

[0014] A fourth aspect of the present invention provides an electronic product housing, wherein the electronic product housing contains the zirconia ceramic provided in the first aspect or the zirconia ceramic provided in the third aspect.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] (1) The zirconia ceramic provided by the present invention satisfies the following properties simultaneously: low light transmittance, high impact resistance, high toughness, low density, low dielectric constant, low hardness and easy processing by limiting the element content and composition in the zirconia ceramic, as well as the synergistic effect of specific elements and specific compositions; specifically, the present invention controls "based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements, 20.65-59.18wt% of Zr, 0.82-3.01wt% of Y, 7.07-53.03wt% of Ln, and 3.49-28.7wt% of Al, wherein Ln is selected from at least one of La, Eu, Nd, Gd, Ce and Sm" and "the zirconia ceramic includes: 30-63wt% of tetragonal zirconia and 37-70wt% of a secondary phase, and the secondary phase includes LnAl 11 O 18 The technical characteristics of "and / or LnAlO3", as well as the synergistic effect between the two, make the zirconia ceramics meet the following requirements: hardness ≤ 1450Hv; toughness ≥ 4MPa·m 1 / 2 ; Transmittance (800nm) ≤1.5%; Dielectric constant ≤29; Density ≤6.15g / cm 3 ; Thinning speed ≥ 25 wires / h; average drop weight height ≥ 20cm.

[0017] (2) The method provided by the present invention simplifies the process flow and is convenient for industrial production; in particular, by lowering the sintering temperature, energy saving and consumption reduction as well as production cost reduction can be achieved. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] The first aspect of the present invention provides a zirconia ceramic, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements: 20.65-59.18wt% Zr, 0.82-3.01wt% Y, 7.07-53.03wt% Ln, 3.49-28.7wt% Al, wherein Ln is selected from at least one of La, Eu, Nd, Gd, Ce and Sm; and the zirconia ceramic comprises: 30-63wt% tetragonal zirconia and 37-70wt% secondary phase, and the secondary phase comprises LnAl 11 O 18 and / or LnAlO3.

[0020] In the present invention, unless otherwise specified, Ln refers to lanthanide elements.

[0021] The inventors of the present invention have found that by adjusting the molar ratio x of Ln (Ln is selected from at least one of La, Eu, Nd, Gd, Ce and Sm) and Al in the zirconia ceramic to satisfy: 1:11≤x≤1:1, the secondary phase in the zirconia ceramic contains LnAl 11 O 18 and / or LnAlO3; specifically, when 1:11<x<1:1, the secondary phase contains LnAl 11 O 18 and LnAlO3; when x = 1:11, the secondary phase contains LnAl 11 O 18 When x = 1:1, the secondary phase contains LnAlO3, by defining the specific structure of the secondary phase, especially by LnAl 11 O 18 The synergistic effect of whiskers and LnAlO3 perovskite makes zirconia ceramics have the characteristics of low transmittance, high impact resistance, low density, low dielectric constant, low hardness, high toughness and easy processing. It can be widely used in the preparation of electronic product casings, especially mobile phone back casings.

[0022] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio x of Ln to Al satisfies: 1:11<x<1:1, the secondary phase comprises LnAl 11 O 18 And LnAlO3. This arrangement is more conducive to improving the impact resistance of zirconia ceramics.

[0023] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio x of Ln and Al satisfies: 1:11<x<1:1, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises: 30-63wt% tetragonal zirconia, 18.5-35wt% LnAl 11 O 18 and 18.5-35wt% LnAlO3.

[0024] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio x of Ln to Al satisfies: x=1:11, the secondary phase comprises LnAl 11 O 18 .

[0025] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio x of Ln to Al satisfies: x=1:11, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia and 37-70wt% of LnAl 11 O 18 .

[0026] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio x of Ln to Al satisfies: x=1:1, the secondary phase comprises LnAlO3.

[0027] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio x of Ln and Al satisfies: x=1:1, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia and 37-70wt% of LnAlO3.

[0028] In some embodiments of the present invention, preferably, in the zirconia ceramic, LnAl 11 O 18 In the present invention, LnAlO3 exists in the form of whiskers and LnAlO3 exists in the form of perovskite. 11 O 18 Whiskers can improve the mechanical properties of zirconia ceramics; LnAlO3 perovskite can reduce the sintering temperature.

[0029] In some embodiments of the present invention, in order to further take into account the mechanical properties of zirconia ceramics, preferably, LnAl 11 O 18 The aspect ratio of the whiskers is ≥4:1, preferably 4-7:1.

[0030] In the present invention, the zirconia ceramic may also contain other elements, such as O; the sum of all elements contained in the zirconia ceramic is 100wt%.

[0031] In the present invention, unless otherwise specified, the content parameters of each element can be tested by XRF using an energy dispersive X-ray fluorescence spectrometer EDX-7000.

[0032] In the present invention, in order to further make the zirconia ceramic have low light transmittance, high impact resistance, low density, low dielectric constant, low hardness, high toughness and easy processing. Preferably, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 38.61-56.36wt% Zr, 1.09-2.86wt% Y, 7.64-45.45wt% Ln, 3.78-24.6wt% Al; the zirconia ceramic includes: 40-60wt% tetragonal zirconia and 40-60wt% secondary phase.

[0033] In the present invention, unless otherwise specified, the content of the phase (e.g., tetragonal zirconia, secondary phase, etc.) in the zirconia ceramic can be determined by XRD. In the XRD spectrum, the diffraction peak of the tetragonal phase of zirconia appears, which may be a solid solution formed by yttrium oxide and zirconia. Preferably, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; further preferably, the content of yttrium oxide in the tetragonal zirconia is 2.6-6.93wt%. The zirconia ceramic may also contain other phases, but they have no negative impact on the zirconia ceramic of the present invention.

[0034] In a specific embodiment of the present invention, in the zirconia ceramic, when the molar ratio x of Ln and Al satisfies: 1:11<x<1:1, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 20.65-59.18wt% Zr, 0.82-3.01wt% Y, 7.07-53.03wt% Ln, and 3.49-28.7wt% Al; preferably, the zirconia ceramic contains, in terms of elements: 38.61-56.36wt% Zr, 1.09-2.86wt% Y, 7.64-45.45wt% Ln, and 3.78-24.6wt% Al.

[0035] In a specific embodiment of the present invention, in the zirconia ceramic, when the molar ratio x of Ln and Al satisfies: x=1:11, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 20.65-56.36wt% of Zr, 1.09-2.86wt% of Y, 7.64-45.45wt% of Ln, and 16.4-28.7wt% of Al.

[0036] In a specific embodiment of the present invention, in the zirconia ceramic, when the molar ratio x of Ln and Al satisfies: x=1:1, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 20.65-59.18wt% Zr, 0.82-3.01wt% Y, 7.07-53.03wt% Ln, and 3.49-28.7wt% Al; preferably, the zirconia ceramic contains, in terms of elements: 38.61-56.36wt% Zr, 1.09-2.86wt% Y, 7.64-45.45wt% Ln, and 3.78-24.6wt% Al.

[0037] In some embodiments of the present invention, based on the total amount of the zirconia ceramic, the zirconia ceramic further comprises: 0-0.5wt% of monoclinic zirconia. In the present invention, the content of the phases included in the zirconia ceramic is based on the zirconia ceramic. The sum of all phases included in the zirconia ceramic is 100wt%.

[0038] When the element composition and phase structure of the zirconia ceramic provided by the present invention contain the above composition, the light transmittance and impact resistance of the zirconia ceramic are improved.

[0039] According to the present invention, when the zirconia ceramic contains the above-mentioned specific contents of various elements and compositions, a synergistic effect can be produced, so that the zirconia ceramic has the characteristics of low light transmittance, high impact resistance, low dielectric constant, low hardness, high toughness, low density and easy processing. Outside the above-defined range, the obtained zirconia ceramic cannot have low light transmittance, high impact resistance, low hardness, high toughness, low density, low dielectric constant and easy processing at the same time.

[0040] The zirconia ceramic provided by the present invention satisfies: hardness ≤ 1450 Hv. It can be seen that the zirconia ceramic provided by the present invention has low hardness.

[0041] The zirconia ceramic provided by the present invention can have a toughness of ≥4MPa·m 1 / 2 It can be seen that the zirconia ceramic has high toughness.

[0042] The light transmittance (800nm) of the zirconia ceramic provided by the present invention is ≤1.5%. Therefore, it can be seen that the zirconia ceramic has a low light transmittance.

[0043] The zirconia ceramic provided by the present invention has low dielectric constant and low density parameters, achieving lightweight. Preferably, the dielectric constant of the zirconia ceramic is ≤29, and the density of the zirconia ceramic is ≤6.15 g / cm 3 .

[0044] In the present invention, measuring the thinning speed of the zirconia ceramic can reflect the processability of the zirconia ceramic. Preferably, the zirconia ceramic satisfies: the thinning speed ≥ 25 wires / h. Among them, the faster the copper plate thinning speed, the faster the processing speed, the higher the efficiency and the lower the cost in production. It can be seen that the zirconia ceramic can have good processability.

[0045] In the present invention, in the drop weight impact test results of the zirconia ceramic, the average drop weight height is ≥ 20 cm, which shows that the zirconia ceramic can have high impact resistance.

[0046] In the present invention, unless otherwise specified, the hardness parameter and toughness parameter are measured using a hardness tester and an indentation method (diamond indenter, force 10 kg, test pressure time 15 s); the transmittance parameter is measured using a Shimadzu spectrophotometer; the dielectric constant parameter is measured using a network analyzer to test the material at 2 GHz; the density parameter is measured using a drainage method; the thinning speed parameter is measured using the dimensional speed under the copper grinding disc, such as a fixed time of 1 h, and the thickness difference before and after copper grinding is tested; the average drop hammer height parameter is measured using a drop hammer impact tester, the sample is placed on a platform, and a 60 g drop hammer is used to hit the center of the sample, starting from a height of 5 cm, if there is no crack, the height is increased by 5 cm each time until visible cracks appear on the sample, and the height value is recorded.

[0047] The zirconia ceramic provided by the present invention can have low light transmittance, high impact resistance, low hardness, high toughness, low dielectric constant and low density, while having better processability. According to the present invention, preferably, the zirconia ceramic simultaneously satisfies: hardness ≤ 1450Hv; toughness ≥ 4MPa·m 1 / 2 ; Transmittance (800nm) ≤1.5%; Dielectric constant ≤29; Density ≤6.15g / cm 3 ; Thinning speed ≥ 25 wires / h; average drop weight height ≥ 20cm.

[0048] According to a particularly preferred embodiment of the present invention, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements, 20.65-59.18wt% of Zr, 0.82-3.01wt% of Y, 7.07-53.03wt% of Ln, and 3.49-28.7wt% of Al, wherein Ln is selected from at least one of La, Eu, Nd, Gd, Ce, and Sm; the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia, 37-70wt% of a secondary phase, and 0-0.5wt% of monoclinic zirconia; the tetragonal zirconia is a solid solution of yttrium oxide and zirconium oxide;

[0049] When the molar ratio x of Ln to Al satisfies: 1:11<x<1:1, the secondary phase contains LnAl 11 O 18 and LnAlO3;

[0050] When the molar ratio x of Ln to Al satisfies: x=1:11, the secondary phase contains LnAl 11 O 18 ;

[0051] When the molar ratio x of Ln to Al satisfies: x=1:1, the secondary phase contains LnAlO 3 .

[0052] A second aspect of the present invention provides a method for preparing a zirconia ceramic, the method comprising the following steps:

[0053] (1) adding water, a dispersant and a binder to powders of zirconium oxide containing yttria, lanthanide oxides and aluminum oxide for wet grinding to obtain a slurry;

[0054] (2) drying the slurry to obtain composite zirconium oxide powder;

[0055] (3) molding and sintering the composite zirconium oxide powder in sequence to obtain a zirconium oxide ceramic;

[0056] Wherein, Ln in the lanthanide oxide is selected from at least one of La, Eu, Nd, Gd, Ce and Sm;

[0057] The molar ratio y of the lanthanide oxide and aluminum oxide satisfies: 1:11≤y≤1:1, wherein the lanthanide oxide is calculated as Ln and the aluminum oxide is calculated as Al.

[0058] According to the present invention, in step (1), the yttria-containing zirconium oxide, lanthanide oxide and aluminum oxide powders can be provided in the form of high-purity powders alone or in combination. For example, yttria and zirconium oxide can be provided by using zirconium oxide powders (with a median particle size of 0.3-0.6 μm and a specific surface area of ​​7-13 m2) containing 1.5-4 mol% yttria. 2 / g), wherein the content of yttrium oxide is based on zirconium oxide; the lanthanide oxide can be a powder with a median particle size of 8-10μm; and the aluminum oxide can be a powder with a median particle size of 0.15-0.6μm.

[0059] In the present invention, step (1) is to grind the powders of various oxides as raw materials, reduce the particle size and obtain slurry. The grinding process is wet grinding, and the specific process may include: mixing the powders of various oxides and water into slurry, first ball milling and mixing, and then sand milling to make the median particle size of various oxides reach nanometer level (such as 250-500nm). More specifically, the various oxides are ball milled for 8-10 hours in a ball mill according to the content of the present invention, and then a dispersant and water are added to a sand mill for sand milling for 8-10 hours, and finally a suitable proportion of binder (such as polyvinyl alcohol and / or polyethylene glycol 4000, which is conducive to powder molding) is added to form a slurry for spraying. The ball mill and the sand mill use zirconia ceramic linings and zirconia grinding balls. The selected particle size of the zirconia grinding balls, the ratio of grinding balls with different particle sizes, the weight ratio of grinding balls to powder, and the amount of water can be controlled to achieve the desired particle size of the oxide.

[0060] In the present invention, unless otherwise specified, the powder is composed of yttria-containing zirconium oxide, lanthanide oxides and aluminum oxide, and the amounts of various materials are such that the composition requirements of the obtained zirconium oxide ceramics are finally met.

[0061] In some embodiments of the present invention, preferably, in step (1), based on the total amount of the powder, the powder contains 40-60wt% of zirconium oxide, 9.01-45.7wt% of lanthanide oxides and 14.3-46.49wt% of aluminum oxide, and the zirconium oxide contains 1.5-4mol% of yttrium oxide.

[0062] In a specific embodiment of the present invention, in step (1), when the molar ratio y of the lanthanide oxide and alumina satisfies: 1:11<y<1:1, based on the total amount of the powder, 40-60wt% of zirconium oxide, 9.01-45.7wt% of lanthanide oxide and 14.3-30.99wt% of alumina, and the zirconium oxide contains 1.5-4mol% of yttrium oxide.

[0063] In a specific embodiment of the present invention, in step (1), when the molar ratio y of the lanthanide oxide and alumina satisfies: y=1:11, based on the total amount of the powder, the powder contains 40-60wt% of zirconium oxide, 9.01-13.51wt% of lanthanide oxide and 30.99-46.49wt% of alumina, and the zirconium oxide contains 1.5-4mol% of yttrium oxide.

[0064] In a specific embodiment of the present invention, in step (1), when the molar ratio y of the lanthanide oxide and alumina satisfies: y=1:1, based on the total amount of the powder, 40-60wt% of zirconium oxide, 9.01-45.7wt% of lanthanide oxide and 14.3-46.49wt% of alumina, and the zirconium oxide contains 1.5-4mol% of yttrium oxide.

[0065] In some embodiments of the present invention, the powder may also contain negligible impurities that do not affect the properties of the zirconia ceramic of the present invention, and the sum of the materials in the powder meets 100wt%.

[0066] In the present invention, the dispersant can promote uniform mixing of the components in the powder. Preferably, in step (1), the dispersant is selected from at least one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and triethanolamine. In the present invention, the dispersant can be commercially available.

[0067] In some embodiments of the present invention, preferably, the amount of the dispersant added is 0.005-0.5wt% of the powder, for example, 0.005wt%, 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.5wt%, and any value in the range composed of any two values, preferably 0.01-0.1wt%.

[0068] In the present invention, the binder is beneficial to the formability of the powder. Preferably, the binder is selected from polyvinyl alcohol and / or polyethylene glycol. Preferably, the binder is polyvinyl alcohol and polyethylene glycol. More preferably, the molar ratio of polyvinyl alcohol to polyethylene glycol is 1:1-2, preferably 1:1. Wherein, the average molecular weight of polyvinyl alcohol is 60000-200000 g / mol; the average molecular weight of polyethylene glycol is 2000-6000 g / mol. In the present invention, the binders are all commercially available.

[0069] In some embodiments of the present invention, preferably, the amount of the binder added is 0.5-5wt% of the powder, for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, and any value in the range of any two values, preferably 2-5wt%.

[0070] In some embodiments of the present invention, preferably, the solid content of the slurry is 20-60wt%, for example, 20wt%, 25wt%, 30wt%, 40wt%, 50wt%, 55wt%, 60wt%, and any value in the range of any two values, preferably 25-55wt%. Such a setting is more conducive to the abrasive effect.

[0071] In the present invention, step (2) can adopt various drying methods, such as spray drying, to form spherical powder with strong fluidity. Preferably, the inlet air temperature of the spray drying is 220-280°C, the outlet air temperature is 100-120°C, and the centrifugal speed is 10-20rpm.

[0072] According to the present invention, step (3) can be used to prepare composite zirconium oxide powder into ceramics. The composite zirconium oxide powder can be first molded and then sintered. Preferably, the molding method includes but is not limited to dry pressing molding, isostatic pressing molding, injection molding, and hot die casting molding, preferably dry pressing molding, which can be molded using a press with a tonnage of 180-200 tons and an oil pressure of 8MPa, such as the shape of a mobile phone back cover.

[0073] According to the present invention, the sintering may be sintering in air. Preferably, in step (3), the sintering conditions include: a temperature of 1400-1600°C, preferably 1450-1550°C; and a sintering time of 1-5h, preferably 1-2h.

[0074] In some embodiments of the present invention, the ceramic obtained by sintering and / or re-sintering is further subjected to flat grinding and polishing, and then cut into a final product using a laser.

[0075] The third aspect of the present invention provides a zirconia ceramic prepared by the method provided in the second aspect. The zirconia ceramic has the advantages of low light transmittance, high impact resistance, low density, low dielectric constant, high toughness, high impact resistance and easy processing.

[0076] The fourth aspect of the present invention provides an electronic product housing, the electronic product housing comprising the zirconia ceramic provided in the first aspect or the zirconia ceramic provided in the third aspect. In the present invention, the electronic product housing includes but is not limited to a mobile phone back shell.

[0077] The present invention will be described in detail below by way of examples. In the following examples,

[0078] Fracture toughness K ic : Hardness tester indentation method (diamond indenter, force 10kg, test time 15s);

[0079] Hardness Hv: hardness tester and indentation method (diamond indenter, force 10kg, test time 15s);

[0080] Processability: The speed of the copper grinding disc under the dimensional test, for example, the fixed time is 1h, and the thickness difference before and after the copper grinding is tested, which is recorded as the thinning speed, wire / h;

[0081] Density: The average number of pits (greater than 20 μm) within a range of 10×10 mm on the large surface of the polished sample;

[0082] Drop hammer impact: Use a drop hammer impact tester (manufacturer CKSI, model E602SS), place the sample on the platform, and use a 60g drop hammer to hit the center of the sample, starting from a height of 5cm. If there is no crack, increase the height by 5cm each time until visible cracks appear on the sample, and record the height value;

[0083] Light transmittance: tested using Shimadzu spectrophotometer;

[0084] Dielectric constant: Use a network analyzer to test the dielectric constant of the material at 2GHz;

[0085] Density parameters were measured using the displacement method;

[0086] XRD test: Use X-ray diffractometer Smartlab (3kW) to test the phase type and content;

[0087] XRF detection: Energy dispersive X-ray fluorescence spectrometer EDX-7000 was used to test the element content of the polished samples.

[0088] Example 1

[0089] Raw materials: 200g of composite powder, which contains 24.66wt% of lanthanum oxide (La2O3), 25.34wt% of aluminum oxide (Al2O3), and 50wt% of zirconium oxide powder stabilized with 3mol% yttria; 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:3.2.

[0090] The raw material was ball-milled in a ball mill for 8 hours with water, and then 0.02 wt% of dispersant (hydroxypropyl methylcellulose) and water were added to a sand mill for 10 hours, and finally 4 wt% of binder (PEG-4000 and PVA with a molar ratio of 1:1) was added to the powder and stirred for 0.5 hours to form a spray slurry with a solid content of 25 wt%;

[0091] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, and centrifugal speed is 15 rpm) to form a composite zirconium oxide powder with strong fluidity for dry pressing;

[0092] The spherical composite zirconia powder is dry-pressed (a 200-ton press uses an 8 MPa oil pressure); the molded powder is sintered at 1450° C. for 2 h, and the sintered product is polished and laser cut to produce zirconia ceramic S1.

[0093] The prepared zirconia ceramic S1 was subjected to high-energy XRF detection. Based on the total amount of the zirconia ceramic S1, the constituent elements of the zirconia ceramic S1 were: 35.5wt% Zr, 2.1wt% Y, 21.2wt% La, 13.5wt% Al, and the molar ratio of La to Al was x=1:3.2.

[0094] The obtained zirconia ceramic S1 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S1, the zirconia ceramic S1 included: 49.4wt% tetragonal zirconia, 50.3wt% secondary phase (LaAl 11 O 18 25.1wt%, LaAlO3 25.2wt%), monoclinic zirconia 0.3wt%. Tetragonal zirconia is a solid solution of yttrium oxide and zirconium oxide.

[0095] Example 2

[0096] Raw materials: 200g of composite powder, which contains 19.73wt% of lanthanum oxide (La2O3), 20.27wt% of aluminum oxide (Al2O3), and 60wt% of zirconium oxide powder stabilized with 3mol% yttria; 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:3.2.

[0097] The raw material was ball-milled in a ball mill for 8 hours with water, and then 0.02 wt% of dispersant (hydroxypropyl methylcellulose) and water were added to a sand mill for 10 hours, and finally 4 wt% of binder (PEG-4000 and PVA with a molar ratio of 1:1) was added to the powder and stirred for 0.5 hours to form a spray slurry with a solid content of 25 wt%;

[0098] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, and centrifugal speed is 15 rpm) to form a composite zirconium oxide powder with strong fluidity for dry pressing;

[0099] The spherical composite zirconia powder is dry-pressed (a 200-ton press uses an oil pressure of 8 MPa); the molded powder is sintered at 1450°C for 2 hours, and the sintered product is polished and laser cut to produce zirconia ceramic S2.

[0100] The prepared zirconia ceramic S2 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S2, the constituent elements of zirconia ceramic S2 were: 42.5wt% Zr, 2.5wt% Y, 17.5wt% La, 10.9wt% Al, and the molar ratio of La to Al was x=1:3.2.

[0101] The obtained zirconia ceramic S2 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S2, the zirconia ceramic S2 included: 59.3wt% tetragonal zirconia, 40.5wt% secondary phase (LaAl 11 O 18 20.2wt%, LaAlO3 20.3wt%), monoclinic zirconia 0.2wt%. Among them, tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0102] Example 3

[0103] Raw materials: 200g of composite powder, which contains 29.59wt% of lanthanum oxide (La2O3), 30.41wt% of aluminum oxide (Al2O3), and 40wt% of zirconium oxide powder stabilized with 3mol% yttria; 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:3.2.

[0104] The raw material was ball-milled in a ball mill for 8 hours with water, and then 0.02 wt% of dispersant (hydroxypropyl methylcellulose) and water were added to a sand mill for 10 hours, and finally 4 wt% of binder (PEG-4000 and PVA with a molar ratio of 1:1) was added to the powder and stirred for 0.5 hours to form a spray slurry with a solid content of 25 wt%;

[0105] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, and centrifugal speed is 15 rpm) to form a composite zirconium oxide powder with strong fluidity for dry pressing;

[0106] The spherical composite zirconia powder is dry-pressed (a 200-ton press uses an oil pressure of 8 MPa); the molded powder is sintered at 1450° C. for 2 h, and the sintered product is polished and laser cut to produce zirconia ceramic S3.

[0107] The prepared zirconia ceramic S3 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S3, the constituent elements of zirconia ceramic S3 were: 28.5wt% Zr, 1.9wt% Y, 25.4wt% La, 16.2wt% Al, and the molar ratio of La to Al was x=1:3.2.

[0108] The obtained zirconia ceramic S3 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S3, the zirconia ceramic S3 included: 39.4wt% tetragonal zirconia, 60.4wt% secondary phase (LaAl 11 O 18 30.1wt%, LaAlO3 30.3wt%), monoclinic zirconia 0.2wt%. Among them, tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0109] Example 4

[0110] Raw materials: 200g of composite powder, which contains 25.27wt% samarium oxide (Sm2O3), 24.73wt% aluminum oxide (Al2O3), and 50wt% zirconium oxide powder stabilized with 3mol% yttria; 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:3.3.

[0111] The raw material was ball-milled in a ball mill for 8 hours with water, and then 0.02 wt% of dispersant (hydroxypropyl methylcellulose) and water were added to a sand mill for 10 hours, and finally 4 wt% of binder (PEG-4000 and PVA with a molar ratio of 1:1) was added to the powder and stirred for 0.5 hours to form a spray slurry with a solid content of 25 wt%;

[0112] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, and centrifugal speed is 15 rpm) to form a composite zirconium oxide powder with strong fluidity for dry pressing;

[0113] The spherical powder of the composite zirconia powder is dry-pressed (a 200-ton press uses an oil pressure of 8 MPa); the molded powder is sintered at 1480°C for 2 hours, and the sintered product is polished and laser cut to produce zirconia ceramic S4.

[0114] The prepared zirconia ceramic S4 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S4, the constituent elements of zirconia ceramic S4 were: 35.4wt% Zr, 2.2wt% Y, 21.9wt% Sm, 13.2wt% Al, and the molar ratio of Sm to Al was x=1:3.3.

[0115] The obtained zirconia ceramic S4 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S4, the zirconia ceramic S4 included: 49.4wt% tetragonal zirconia, 50.3wt% secondary phase (SmAl 11 O 18 25.1wt%, SmAlO3 25.2wt%), monoclinic zirconia 0.3wt%. Among them, tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0116] Example 5

[0117] Raw materials: 200g of composite powder, which contains 11.25wt% of lanthanum oxide (La2O3), 38.75wt% of aluminum oxide (Al2O3), and 50wt% of zirconium oxide powder stabilized with 3mol% yttria; 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:11.

[0118] The raw material was ball-milled in a ball mill for 8 hours with water, and then 0.02 wt% of dispersant (hydroxypropyl methylcellulose) and water were added to a sand mill for 10 hours, and finally 4 wt% of binder (PEG-4000 and PVA with a molar ratio of 1:1) was added to the powder and stirred for 0.5 hours to form a spray slurry with a solid content of 25 wt%;

[0119] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, and centrifugal speed is 15 rpm) to form a composite zirconium oxide powder with strong fluidity for dry pressing;

[0120] The spherical composite zirconia powder is dry-pressed (a 200-ton press uses an oil pressure of 8 MPa); the molded powder is sintered at 1450° C. for 2 h, and the sintered product is polished and laser cut to produce zirconia ceramic S5.

[0121] The prepared zirconia ceramic S5 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S5, the constituent elements of zirconia ceramic S5 were: 35.4wt% Zr, 2.1wt% Y, 9.7wt% La, 20.7wt% Al, and the molar ratio of La to Al was x=1:11.

[0122] The obtained zirconia ceramic S5 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S5, the zirconia ceramic S5 included: 49.5wt% tetragonal zirconia, 50.3wt% secondary phase (LaAl 11 O 18 ), the monoclinic zirconium oxide is 0.2wt%. The tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0123] Example 6

[0124] The method of Example 5 is different in that the composition of the raw materials is different, that is, 200g of composite powder, which contains 9.01wt% of lanthanum oxide (La2O3), 30.99wt% of aluminum oxide (Al2O3), and 60wt% of zirconium oxide powder stabilized with 3mol% yttria, wherein La2O3 is used as the raw material. 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:11; the other conditions are the same, and zirconia ceramic S6 is obtained.

[0125] The prepared zirconia ceramic S6 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S6, the constituent elements of zirconia ceramic S6 were: 42.4wt% Zr, 2.5wt% Y, 7.8wt% La, 16.6wt% Al, and the molar ratio of La to Al was x=1:11.

[0126] The obtained zirconia ceramic S6 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S6, the zirconia ceramic S6 included: 59.6wt% tetragonal zirconia, 40.1wt% secondary phase (LaAl 11 O 18 ), the monoclinic zirconium oxide is 0.3wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0127] Example 7

[0128] The method of Example 5 is different in that the composition of the raw materials is different, that is, 200g of composite powder, which contains 13.5wt% of lanthanum oxide (La2O3), 46.49wt% of aluminum oxide (Al2O3), and 40wt% of zirconium oxide powder stabilized with 3mol% yttria, wherein La2O3 is used as the raw material. 3+ Lanthanum oxide and Al 3+The molar ratio y of aluminum oxide is 1:11; the other conditions are the same, and the zirconia ceramic S7 is obtained.

[0129] The prepared zirconia ceramic S7 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S7, the constituent elements of zirconia ceramic S7 were: 28.4wt% Zr, 1.8wt% Y, 11.6wt% La, 24.9wt% Al, and the molar ratio of La to Al was x=1:11.

[0130] The obtained zirconia ceramic S7 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S7, the zirconia ceramic S7 included: 39.5wt% tetragonal zirconia, 60.1wt% secondary phase (LaAl 11 O 18 ), the monoclinic zirconium oxide is 0.4wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0131] Example 8

[0132] The method of Example 5 is different in that the composition of the raw materials is different, that is, 200g of composite powder, which contains 11.85wt% of samarium oxide (Sm2O3), 38.15wt% of aluminum oxide (Al2O3), and 50wt% of zirconium oxide powder stabilized with 3mol% yttria, wherein Sm 3+ Lanthanum oxide and Al 3+ The molar ratio y of aluminum oxide is 1:11; the other conditions are the same, and zirconia ceramic S8 is obtained.

[0133] The prepared zirconia ceramic S8 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S8, the constituent elements of zirconia ceramic S8 were: 35.5wt% Zr, 2.2wt% Y, 10.3wt% Sm, 20.4wt% Al, and the molar ratio of Sm to Al was x=1:11.

[0134] The obtained zirconia ceramic S8 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S8, the zirconia ceramic S8 included: 49.6wt% tetragonal zirconia, 50.1wt% secondary phase (SmAl 11 O 18 ), the monoclinic zirconium oxide is 0.3wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0135] Example 9

[0136] The method of Example 1 is followed, except that the composition of the raw materials is different, that is, 200 g of composite powder, which contains 45.7 wt% of lanthanum oxide (La2O3), 14.3 wt% of aluminum oxide (Al2O3), and 40 wt% of zirconium oxide powder stabilized with 3 mol% yttria; the other conditions are the same, and zirconium oxide ceramic S9 is obtained.

[0137] The prepared zirconia ceramic S9 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic S9, the constituent elements of zirconia ceramic S9 were: 42.3wt% Zr, 2.6wt% Y, 26.1wt% La, 5.1wt% Al, and the molar ratio of La to Al was x=1:1.

[0138] The obtained zirconia ceramic S9 was subjected to XRD detection. Based on the total amount of the zirconia ceramic S9, the zirconia ceramic S9 included: 59.4wt% tetragonal zirconia, 40.1wt% secondary phase (LaAl 11 O 18 0wt%, LaAlO3 is 40.1wt%), and monoclinic zirconia is 0.5wt%. Among them, tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0139] Comparative Example 1

[0140] Raw materials: 200 g of composite powder, including 50 wt% of aluminum oxide (Al2O3) and 50 wt% of zirconium oxide powder stabilized with 3 mol% yttria;

[0141] The raw material was ball-milled in a ball mill for 8 hours with water, and then 0.02 wt% of dispersant (hydroxypropyl methylcellulose) and water were added to a sand mill for 10 hours, and finally 4 wt% of binder (PEG-4000 and PVA with a molar ratio of 1:1) was added to the powder and stirred for 0.5 hours to form a spray slurry with a solid content of 25 wt%;

[0142] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, and centrifugal speed is 15 rpm) to form a composite zirconium oxide powder with strong fluidity for dry pressing;

[0143] The spherical composite zirconia powder was dry-pressed (a 200-ton press used an 8 MPa oil pressure); the molded powder was sintered at 1550° C. for 2 h, and the sintered product was polished and laser cut to produce zirconia ceramic D1.

[0144] The obtained zirconia ceramic D1 was subjected to high-energy XRF detection. Based on the total amount of the zirconia ceramic D1, the constituent elements of the zirconia ceramic D1 were: 35.5wt% Zr, 2.1wt% Y, and 26.6wt% Al.

[0145] The obtained zirconia ceramic D1 was subjected to XRD detection. Based on the total amount of the zirconia ceramic D1, the zirconia ceramic D1 included: 49.6wt% of tetragonal zirconia, 50.1wt% of Al2O3, and 0.3wt% of monoclinic zirconia, wherein the tetragonal zirconia was a solid solution of yttrium oxide and zirconia.

[0146] Comparative Example 2

[0147] The method of Comparative Example 1 is followed, except that the composition of the raw materials is different, that is, 200 g of composite powder contains 100 wt % of zirconia powder stabilized with 3 mol % yttria; the other conditions are the same, and zirconia ceramic D2 is obtained.

[0148] The obtained zirconia ceramic D2 was subjected to high-energy XRF detection. Based on the total amount of the zirconia ceramic D2, the constituent elements of the zirconia ceramic D2 were: Zr was 70.3wt% and Y was 4.3wt%.

[0149] The obtained zirconia ceramic D2 was subjected to XRD detection. Based on the total amount of the zirconia ceramic D2, the zirconia ceramic D2 included: 99.6wt% of tetragonal zirconia and 0.4wt% of monoclinic zirconia, wherein the tetragonal zirconia was a solid solution of yttrium oxide and zirconium oxide.

[0150] Comparative Example 3

[0151] The method of Example 1 is followed, except that the composition of the raw materials is different, that is, 200 g of composite powder, which contains 4 wt% of lanthanum oxide (La2O3), 26 wt% of aluminum oxide (Al2O3), and 70 wt% of zirconium oxide powder stabilized with 3 mol% yttria; the other conditions are the same, and zirconium oxide ceramic D3 is obtained.

[0152] The prepared zirconia ceramic D3 was subjected to high-energy XRF detection. Based on the total amount of zirconia ceramic D3, the constituent elements of zirconia ceramic D3 were: 49.4wt% Zr, 2.9wt% Y, 3.5wt% La, 13.9wt% Al, and the molar ratio of La to Al was x=1:20.77.

[0153] The obtained zirconia ceramic D3 was subjected to XRD detection. Based on the total amount of the zirconia ceramic D3, the zirconia ceramic D3 included: 69.3wt% tetragonal zirconia, 30.2wt% secondary phase (LaAl 11 O 18 18.1wt%, Al2O3 12.1wt%), monoclinic zirconia 0.3wt%. Tetragonal zirconia is a solid solution of yttrium oxide and zirconium oxide.

[0154] Test Example 1

[0155] The zirconia ceramics (S1-S9 and D1-D3) prepared in Examples 1-9 and Comparative Examples 1-3 were tested for hardness, toughness, density and light transmittance. The results are shown in Table 1.

[0156] Table 1

[0157]

[0158]

[0159] Compared with Comparative Examples 1-3, it can be seen that the zirconia ceramic provided by the present invention has low hardness, high toughness, high density and low transmittance. In particular, by limiting the content of the secondary phase in the zirconia ceramic to a preferred protection range, the hardness, toughness and transmittance of the zirconia ceramic are further optimized.

[0160] It can be seen from Examples 1-3 that when the molar ratio x of La to Al in the zirconia ceramic is the same, the higher the total content of La and Al, the lower the hardness, toughness and light transmittance of the obtained zirconia ceramic.

[0161] Similarly, it can be seen from Examples 5-8 that when the molar ratio x of La and Al in the zirconia ceramic is the same, the higher the total content of La and Al, the lower the hardness, toughness and transmittance of the obtained zirconia ceramic.

[0162] Test Example 2

[0163] The zirconia ceramics (S1-S9 and D1-D3) prepared in Examples 1-9 and Comparative Examples 1-3 were subjected to dielectric constant, density, processability, and drop hammer impact tests. The results are shown in Table 2.

[0164] Table 2

[0165]

[0166]

[0167] Compared with comparative examples 1-3, the zirconia ceramics provided by the present invention simultaneously meet the following requirements: dielectric constant ≤ 29, density ≤ 6.15 g / cm 3 , thinning speed ≥ 25 wires / h, average drop weight height ≥ 20 cm; that is, compared with comparative examples 1-3, the zirconia ceramics provided by the present invention have the advantages of low density, low dielectric constant, high impact resistance and easy processing.

[0168] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A zirconia ceramic, characterized in that: Based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements, 20.65-59.18wt% of Zr, 0.82-3.01wt% of Y, 7.07-53.03wt% of Ln, and 3.49-28.7wt% of Al, wherein Ln is selected from at least one of Eu, Nd, Gd, and Sm; and the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia and 37-70wt% of a secondary phase, and the secondary phase comprises LnAl 11 O 18 and LnAlO3; In the zirconia ceramic, LnAl 11 O 18 It exists in the form of whiskers, and LnAlO3 exists in the form of perovskite.

2. The zirconia ceramic according to claim 1, wherein Based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 38.61-56.36 wt % of Zr, 1.09-2.86 wt % of Y, 7.64-45.45 wt % of Ln, and 3.78-24.6 wt % of Al; The zirconia ceramic comprises: 40-60wt% of tetragonal zirconia and 40-60wt% of secondary phase.

3. The zirconia ceramic according to claim 1 or 2, wherein: The zirconia ceramic meets the requirement of hardness ≤ 1450 Hv.

4. The zirconia ceramic according to claim 3, wherein: The zirconia ceramics meet the following requirements: toughness ≥ 4 MPa·m 1 / 2 .

5. The zirconia ceramic according to claim 1 or 4, wherein: The zirconia ceramic meets the following requirements: 800nm ​​transmittance ≤1.5%.

6. The zirconia ceramic according to claim 5, wherein: The zirconium oxide ceramic satisfies: a dielectric constant ≤ 29.

7. The zirconia ceramic according to claim 1 or 6, wherein: The zirconia ceramic meets the following requirements: density ≤ 6.15 g / cm 3 .

8. The zirconia ceramic according to claim 7, wherein: The zirconia ceramic meets the requirement that the thinning speed is ≥ 25 wires / h.

9. The zirconia ceramic according to claim 1 or 8, wherein: The zirconia ceramic meets the requirement that the average drop height is ≥ 20 cm.

10. The method for preparing the zirconia ceramic according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: (1) adding water, a dispersant and a binder to powders of zirconium oxide containing yttria, lanthanide oxide and aluminum oxide for wet grinding to obtain a slurry; (2) drying the slurry to obtain composite zirconium oxide powder; (3) molding and sintering the composite zirconium oxide powder in sequence to obtain zirconium oxide ceramics; Wherein, Ln in the lanthanide oxide is selected from at least one of Eu, Nd, Gd and Sm; The molar ratio y of the lanthanide oxide and aluminum oxide satisfies: 1:11≤y≤1:1, wherein the lanthanide oxide is calculated as Ln and the aluminum oxide is calculated as Al.

11. The method according to claim 10, wherein: Based on the total amount of the powder, the powder contains 40-60wt% of zirconium oxide, 9.01-45.7wt% of lanthanide oxides and 14.3-46.49wt% of aluminum oxide, and the zirconium oxide contains 1.5-4mol% of yttrium oxide.

12. The method according to claim 10 or 11, wherein: In step (1), the amount of the dispersant added is 0.005-0.5wt% of the powder.

13. The method according to claim 12, wherein: In step (1), the amount of the dispersant added is 0.01-0.1wt% of the powder.

14. The method according to claim 10 or 11, wherein: In step (1), the amount of the binder added is 0.5-5wt% of the powder.

15. The method according to claim 14, wherein: In step (1), the amount of the binder added is 2-5wt% of the powder.

16. The method according to claim 10 or 11, wherein: In step (1), the solid content of the slurry is 20-60wt%.

17. The method according to claim 16, wherein: In step (1), the solid content of the slurry is 25-55wt%.

18. The method according to claim 15 or 17, wherein: In step (3), the molding method is selected from at least one of dry pressing, isostatic pressing, injection molding and hot die casting.

19. The method according to claim 18, wherein: In step (3), the sintering conditions include: temperature of 1400-1600° C. and time of 1-5 h.

20. The method according to claim 19, wherein: In step (3), the sintering conditions include: temperature of 1450-1550°C and time of 1-2h.

21. Zirconia ceramics obtained by the method according to any one of claims 10 to 20.

22. An electronic product housing, characterized in that: The electronic product housing contains the zirconium oxide ceramic according to any one of claims 1 to 9 and 21.

Citation Information

Patent Citations

  • Zirconium oxide-based composite material

    CN104736498A

  • Thermal shock-resistant composite materials

    CN108349817A

  • Articles comprising ceramics and method of making the same

    US20210078908A1